Influence of surgical time on post-surgical visual acuity in patients undergoing small incision cataract surgery: a prospective study - Lathika, Vasu Kamaladevi; Minu, Susan Prakash; Charles, K. Skariah (International Journal of Research in Medical Sciences, 2016)
Background: Cataract surgery is one of the commonest surgical procedures in Ophthalmology. This study aimed at evaluating the influence of duration of surgery on post-operative vision in patients who underwent uneventful small incision cataract surgery. Methods: All patients (66.3±8.6 years of age), who underwent small incision cataract surgery after a complete preoperative evaluation. Duration of surgery starting from draping to sub conjunctival injection of amikacin after surgery was noted. The patients were grouped based on surgical time. Best corrected visual acuity was recorded in all patients on post-operative day one and also one month after surgery. The data was subjected to statistical analysis. Results: Ninety one patients were included in this study. More number of patients (47/91) was found in group with 26-35 min surgical time, whereas only 9 patients were found in 46-55 min group. A week correlation was found between surgical timing with PSVA on 1st (r = 0.2034, 95% CI = -0.00772-0.3971, two tailed p = 0.051) or on the 30th day (r= 0.1024; 95% CI = -0.1107-0.3066, two tailed p =0.33). No significant difference was found in the PSVA of 1st day (p=0.699) or 30th day (p=0.150) when compared between the groups. However, the difference was found to be significant between the mean value of POVA between the 1st and 30th day in all groups. Conclusions: Surgical time did not emerge as a significant influence on long term post-operative visual outcome following uncomplicated Small incision cataract surgery.